Gender and Sustainable Development a New Paradigm/Ana maria Basileriro - Brasileiro Ana Maria (United States Misc. Pacific Islands, 1996)
Trata de gender and Sustainable Development a New Paradigm.
1.Women and the environment in ecuador 2.Women as conservation allies
incluye índice
Col. Gen
Keywords: 1.AN ISLAN VISION:SUSTAINABLE DEVELPMENT 2.WOMEN AND THE ENVIRONMENT